A simulation of dataflow computer models and a model of fault tolerant dataflow computer - Ojsteršek, Milan (Informatica (Ljubljana), 1987)
Dataflow architectures are very promising since they have the characteristic of asynchrony, functionality and because they enable parallel processing . They are divided into static and dynamic dataflow models. The paper includes the description of the program language DFL1 and the corresponding simulator.
Keywords: arhitekture podatkovno vodene; arhitekture računalniške; computer architectures; computer science; dataflow architectures; dataflow computers; fault tolerance; neobčutljivost na napake; računalniki podatkovno vodeni; računalništvo; simulacija; simulation